Kultura i učenje stranih jezika (Philologia, 2021)
The paper focuses on the relationship between language and culture and the importance it has for a successful foreign language teaching and learning. The examples from several languages are presented to demonstrate the differences in conceptualization and realization of language patterns and the interdependence of linguistic items and cultural models. The firm link between culture and language on the one hand, and the differences between not only L1 and L2, but also between target and native cultures on the other hand, provide for cultural transfer to affect linguistic behaviour, thus necessitating transformation of foreign language learning into a process of simultaneous differentiation and acquisition of both linguistic and cultural practices. Integration of linguistic, cultural and communicative perspectives for the purpose of learning the desired behaviour embedded in communication activities is a part of the development of intercultural competence, which, as comprising attitudes, knowledge, skills and values, should enable communicators to act as culturally aware social agents in multilingual and multicultural environments.
Keywords: culture; language; transfer; behaviour; practice; communication; intercultural competence